Trends in the Uses of Spirulina Microalga: A mini-review - Aondohemba Samuel Nege; Endang Dewi Masithah; Junaidi Khotib (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
HighlightsTrends in the uses of Spirulina over different decades were critically examinedFindings from surveyed literature indicated that Spirulina utilization was mainly focused on its food and feed potential before the last 20-30 yearsThe review observed that research focused on the health and pharmaceutical uses, biofertilizer, bioplastic, cosmetic, bioenergy and pollution control applications of Spirulina are trends that sprouted out within the last 20-25 years.The review has successfully compiled numerous uses of Spirulina microalga for easy readership by readers since many studies have been performed on the uses Spirulina but reviews of this type spanning through different beneficial aspects of  Spirulina are still scarce. Hence, this review fills such gap.       AbstractThere is a need to have a single document that summarises the present day uses of Spirulina. In this review, the research trend on the health and other applications of Spirulina microalga was critically evaluated. In terms of the health uses, antioxidant, antibacterial, and immunostimulant effects of Spirulina were emphasized. Other uses of the microalga discussed include the use of Spirulina for human and animal food, bioenergy, pollution and ecotoxicology control, cosmetics, bioplastics and biofertilizers. Literature search revealed that Spirulina polysaccharides, phycocyanin size and content play a role in antioxidant activity and DNA repair. The double bonds and positions of –COOH and –OH in Spirulina phenol content and Î³-linolenic fatty acids (Î³-LFA) have antimicrobial activity. Some compounds in Spirulina improve immune, increase survival rate and enhance distribution of proteins like hepcidin and TNF-α in animal models. High protein, vitamins, fatty acids (FAs) and glycoproteins in Spirulina are easily digestible due to its lack of cellulose and can improve human and livestock growth. Spirulina produces biodegradable and non-toxic biodiesel and useful co-products. Absorption of heavy metals by chemisorption occurs in Spirulina. Phycocyanin and β-carotene of Spirulina increase skin health, Spirulina also cause high cell proliferation and aids wound healing. Bioplastics produced from Spirulina are biodegradable, non-toxic with high blends. Biofertilizers from Spirulina have little or no residual risks, adds soil Nitrogen through Spirulina Nitrogen fixation ability. In addition, the survey of published works on Spirulina for the past two decades indicates that more research is been carried out in recent years using Spirulina, especially studies involving its health potentials and those concerned with molecular analysis. In conclusion, Spirulina is an exceptional commodity with numerous applications, and probably, some of its compounds causing those effects are yet to be isolated and that is one area for further research.